An Experimental Test of the Effects of Hurricane News about Human Behavior on Climate-Related Attitudes. Issue 6 (17th August 2020) - Myrick, Jessica Gall; Conlin, Jeff
ABSTRACT: The year 2017 was an historic season for hurricanes devastating the United States. Related news coverage brought people close to the impacts of these natural disasters through evocative stories of people acting as heroes and villains, showing humanity at its best and worst. The current study experimentally tested the potential for these news stories of human responses to hurricanes to shape emotional and moral responses of viewers. The study also examined how hurricane news could subsequently influence other perceptions, including the implicit link between climate change and hurricane intensity and frequency. Results showed that news stories featuring the best and worst of humanity were both effective at evoking compassion, yet only stories featuring the worst of humanity evoked anger. Both emotions' relationships with moral conviction, policy attitudes, and behavioral intentions toward climate change were mediated by reflection, and further analyses revealed significant differences among conservative, moderate, and liberal audiences.